DETERMINATION OF AMINO ACIDS AND OIL SOLUBLE VITAMINS COMPOSITION OF SOME SMALL INDIGENOUS FISHES OF MANIPUR, INDIA - MAYANGLAMBAM, SHANTOSH; TONGBRAM, SEITYAMALA; CHUNGKHAM, SAROJNALINI (Journal of the Inland Fisheries Society of India, 2026)
In this study, we aimed to determine the amino acids content, essential amino acids score and oil soluble Vitamins content in the Small indigenous fishes of Manipur, India. The amino acids and oil soluble Vitamins viz. Vit-A, Vit-D, Vit-E and Vit-K composition of the fishes are analysed by using HPLC. 16 different amino acids which categorized under essential amino acids (EAAs) and non-essential amino acids (NEAAs) were determined. As the result of the analysis threonine which is followed by leucine and histamine are the most abundant EAAs found in the fishes. Whereas, arginine, glycine and alanine are the predominant NEAAs found in the fishes. The ratio of the NEAAs and EAAs are also calculate, which index the quality of protein found in the fishes. The ratio ranges from 0.79 g/100g (Lepidochephalichthys guntea) - 5.98 g/100g (Hypsibarbus myitkyinae). The essential amino acids scores are shown higher than the reference (g/100g) given by FAO/WHO/UNU, 2007. The oil soluble vitamins viz. Vitamin A, Vitamin D, Vitamin E and Vitamin K were found in the ranged of 7.26 µg/100g (Hypsibarbus myitkyinae) to 18.50 µg/100g (Pangio pangia), 3.48 µg/100g (Syncrossus berdmorei) to 12.89 µg/100g (Tariqilabeo burmanicus), 1.65 µg/100g (Glossogobius giuris) to 0.24 µg/100g (Devario yuensis) and 6.94 µg/100g (Pangio pangia) to 12.76 µg/100g (Glossogobius giuris) respectively. Form the study it is shown that SIFFs can be determined as the good sources of amino acids and oil soluble vitamins. It may also provide the knowledge about the importance of SIFFs for their high nutritive value and good food for monitoring many micro nutrients deficiencies, so consumption of SIFFs should be encouraged.